Provider perceptions of young people living with HIV and unhealthy alcohol use in Southwestern Uganda: a qualitative study - Odokonyero, Raymond Felix; Nakasujja, Noeline; Turiho, Andrew; Sanyu, Naomi; Muyindike, Winnie R.; Nansera, Denis; Semitala, Fred; Kamya, Moses R; Katahoire, Anne R; Hahn, Judith A; Camlin, Carol C.; Muhwezi, Wilson W (BioMed Central, 2024)
Unhealthy alcohol use is a common public health problem in HIV care settings in Africa and it affects the HIV continuum of care. In Uganda and other low-income countries, HIV care providers are a key resource in caring for young people (15-24 years) living with HIV (YPLH) with unhealthy alcohol use. Caring for YPLH largely depends on care providers' perceptions of the problem. However, data that explores HIV care providers' perceptions about caring for YPLH with unhealthy drinking are lacking in Uganda. We sought to describe the perceptions of HIV care providers regarding caring for YPLH with unhealthy drinking in the Immune Suppression Syndrome (ISS) Clinic of Mbarara Regional Referral Hospital in southwestern Uganda.BACKGROUNDUnhealthy alcohol use is a common public health problem in HIV care settings in Africa and it affects the HIV continuum of care. In Uganda and other low-income countries, HIV care providers are a key resource in caring for young people (15-24 years) living with HIV (YPLH) with unhealthy alcohol use. Caring for YPLH largely depends on care providers' perceptions of the problem. However, data that explores HIV care providers' perceptions about caring for YPLH with unhealthy drinking are lacking in Uganda. We sought to describe the perceptions of HIV care providers regarding caring for YPLH with unhealthy drinking in the Immune Suppression Syndrome (ISS) Clinic of Mbarara Regional Referral Hospital in southwestern Uganda.We used semi-structured in-depth interviews (IDIs) to qualitatively explore HIV care providers' perceptions regarding caring for YPLH with unhealthy alcohol use. The study was conducted at the adolescent immunosuppression (ISS) clinic of Mbarara Regional Referral Hospital. Interviews were tape-recorded and transcribed verbatim. Using thematic content analysis, data from 10 interviews were analyzed.METHODSWe used semi-structured in-depth interviews (IDIs) to qualitatively explore HIV care providers' perceptions regarding caring for YPLH with unhealthy alcohol use. The study was conducted at the adolescent immunosuppression (ISS) clinic of Mbarara Regional Referral Hospital. Interviews were tape-recorded and transcribed verbatim. Using thematic content analysis, data from 10 interviews were analyzed.HIV care providers were concerned and intended to care for YPLH with unhealthy alcohol use. They understood that unhealthy drinking negatively impacts HIV care outcomes and used counseling, peer support, and referrals to routinely intervene. They however, did not apply other known interventions such as health education, medications and follow-up visits because these required family and institutional support which was largely lacking. Additional barriers that HCPs faced in caring for YPLH included; gaps in knowledge and skills required to address alcohol use in young patients, heavy workloads that hindered the provision of psychosocial interventions, late payment of and low remunerations, lack of improvement in some YPLH, and inadequate support from both their families and hospital management.RESULTSHIV care providers were concerned and intended to care for YPLH with unhealthy alcohol use. They understood that unhealthy drinking negatively impacts HIV care outcomes and used counseling, peer support, and referrals to routinely intervene. They however, did not apply other known interventions such as health education, medications and follow-up visits because these required family and institutional support which was largely lacking. Additional barriers that HCPs faced in caring for YPLH included; gaps in knowledge and skills required to address alcohol use in young patients, heavy workloads that hindered the provision of psychosocial interventions, late payment of and low remunerations, lack of improvement in some YPLH, and inadequate support from both their families and hospital management.HIV care providers are important stakeholders in the identification and care of YPLH with unhealthy alcohol use in Southwestern Uganda. There is a need to train and skill HCPs in unhealthy alcohol use care. Such training ought to target the attitudes, subjective norms, and perceived control of the providers.CONCLUSIONHIV care providers are important stakeholders in the identification and care of YPLH with unhealthy alcohol use in Southwestern Uganda. There is a need to train and skill HCPs in unhealthy alcohol use care. Such training ought to target the attitudes, subjective norms, and perceived control of the providers. MEDLINE - Academic